Synthesis and cytotoxicity test of LR-2 on breast cancer cell line T47D - Ritmaleni Ritmaleni; Dina Anitasari; Sinta Susanti; Sismindari . (Indonesian Journal of Pharmacy, 2011)
LR-2  is  a  compound  analog  of  monastrol,  an  anticancer  agent,  which  has been succesfully synthesised through the application of Biginelli reaction and one of  LR  compound  series  that  synthesised  in  Faculty  of  Farmacy,  Universitas Gadjah  Mada.  This  reserach  was  aimed  to  synthesized the  LR-2  compound  and to investigate the cytotoxicity of LR-2 on breast cancer cell line. The reaction was carried out by using the one pot reaction method. In this reaction benzaldehyde, 2-indanone and thiourea were reacted together for 6hours in acid catalyst. The cytotoxicity  test  was  carried  by  using  breast  cancer  cell  line  the  MTT  assay method and the LC50 was ditermined by using the probit analysis with Miller and Tainter  method.  The  product  was  isolated  by  using  preparative  TLC  in  54  % yield. The structure was elucidated by spectroscopymethods (UV-Vis, H-NMR, IR and GC-MS).The LC50 is 159 µM.Keywords : LR-2, benzaldehyde, 2-indanone, thiourea, T47D